Assessment of the Therapeutic Communication Skills of Clinicians with Patients in the University of the Philippines Manila College of Dentistry/Gianna Marie L. Marabut. - Marabut, Gianna Marie L.; Ermita, Christian M. (2023)
Introduction: Dental curricula is observed to focus more on the technical skills and
cognitive knowledge of dental students, without great emphasis on communication skills
which are vital to patient care. The study aimed to assess the communications skills of
clinicians with patients in the University of the Philippines Manila College of Dentistry
(UPCD).
Methods: Descriptive cross-sectional study design was used for this research. Matched
survey questionnaires, Student Communication Assessment Instrument (SCAI) and
Patient Communication Assessment Instruments (PCAI), were distributed to 1) clinicians
enrolled in Clinical Conference and Practice for the Second Semester of A.Y. 2018-2019
and were ≥18 years old and 2) patients who were ≥18 years old and had ≥2 appointments
with the same clinician. The data gathered were collated, encoded, and presented in
tabular and graphical forms. Participants remained anonymous, and all methods in this
study were approved by UP Manila Research Ethics Board.
Results: The results of the clinicians’ self-assessment using Student Communication
Assessment Instrument (SCAI) show that students mostly rated themselves 4 (“Very
Good”) or 5 (“Excellent”) in most questions. On the other hand, patients mostly rated their
clinicians 5 (“Excellent”) in all three assessment points. In terms of the inter-agreement
of the communication scores, the mode of ratings of patients is equal or higher than the
self-rating of clinicians.
Conclusion: From the results, it can be concluded that there is no deficiency in the
communication skills of the clinicians from the perspective of both clinicians themselves
and their patients.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental education; Communication; Dentist and patient; Communication in dentistry